Taxonomia do urbanismo tático: uma proposta para leitura, compreensão e articulação das táticas urbanas emergentes - Farias, Ana Carolina Carvalho (2018)
Cities are formed by a set of official practices supported by their normative institutions, and also by unofficial practices, that escape the norms and that bring other possibilities, other urgencies. The term tactical urbanism began to be used in the first decade of the 21st century to designate such practices in urbanism, referring generally to temporary, informal and somewhat contentious urban interventions in official practices and contemporary cities. However, the theoretical, artistic and political references of the practitioners of Tactical Urbanism refer to a much broader and complex role of practices that are often presented as an alternative to the Neoliberal Urbanism, currently hegemonic in the production of cities. However, there is still a certain theoretical and methodological gap regarding the tactical movements of urban production, which make it difficult to understand their capabilities and analyze their effects. In this sense, this research tried to construct a conceptual panorama on the Tactical Urbanism, exemplified with several practitioners and practices, sometimes called as such, sometimes indifferent to the term but within it. For this, a Taxonomy of Tactical Urbanism was elaborated, which brings eleven categories of analysis, elaborated in eighty-four subcategories, with the purpose of providing a reading for such practices and facilitating the articulation between their ideas, agents and objectives. For the elaboration of the Taxonomy, forty practices were charted and cataloged, exemplifying the various narratives that compose the discourse of urban tactics, representative of the work of great exponents of this discourse and also of the urban realities of the five continents. The Taxonomy is available on online platform, which allows the processing of complex data and collaborative data feeding. In this study, we demonstrate several ways of using the Taxonomy of Tactical Urbanism, among them, the triangulation between specific categories with the objective of verifying how Tactical Urbanism contributes in the fight for the right to the city, in the constitution of urban commons and in the confrontation with Neoliberal Urbanism. This articulation allowed us to conclude that the tactical self-denominated practices, closer to what was popularized with the label of Tactical Urbanism, present generally fragile arrangements as alternative possibilities to the neoliberal city, while the practices that are better able to promote the right to the city and to experience the constitution of commons, are those that take the tactic beyond the tactic, combining it in strategic movements, more aligned with the traditional struggles for urban justice. Such a conclusion reveals the need for critical thinking to better subsidize such actions, helping to circumvent the pitfalls and enhance the capacities of collaboration, participation and empowerment of multitude, which Tactical Urbanism can bring as contributions to the construction of more just cities.